Analysis of Factors Affecting Islamic Bank Financing for the Fisheries Sector in Indonesia - Laili, Nur; Tanjung, Hendri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The development of the fisheries sector in Indonesia should get more attention, especially in efforts to increase fishing businesses, limited financial access is still a problem that must be faced by the fisheries sector. Thus, Islamic banking can play a significant role in providing financing for the development of national fisheries. This study analyzes the factors that influence fisheries financing in Islamic banking in Indonesia and how efforts to increase fisheries sector financing. The processed data source is the monthly statistics of the Islamic banking industry from October 2014 to May 2019, and the method of analysis of this study uses VAR / VECM. The results showed that the NPF and PUAS affect fishery financing in the short term negatively and significantly. Whereas in the long term INF, NPF, PUAS, and ISBIS negatively affect fishery financing, as for CAR, and FDR affects fishery financing positively. Furthermore, SBK, and MRP do not affect fishery financing, both short-term and long-term. This study recommends an increase in the proportion of fishery financing along with an increase in Islamic banking capital, increased monitoring of fishery financing, and strengthening of national monetary policy instruments.